I am Bella, star of the show - Stier, Catherine; Rosa, Francesca (Chicago, Illinois : Albert Whitman & Company, 2021)
Bella the Jack Russell terrier loves being in the spotlight, and is very good at acting, but her dog brother, Chewy the German shepherd, always seems to get the big roles. Includes information about the breed and the role of the working dog.
Ages 7-12.
Grades 4-6.
Keywords: Jack Russell terrier -- Juvenile fiction; Jack Russell terrier -- Fiction; Dogs on television -- Fiction; Television -- Production and direction -- Fiction; Working dogs -- Fiction